G252(P) Is Simulation an Effective Method for Teaching Paediatric Emergencies to Final Year Medical Students?. (24th May 2017) - Hayes, A; Grimbley, J; Williams, JD
Abstract : Aims: Simulation is a recognised method of improving skills in clinical emergencies. We have introduced simulation training into the final year medical student paediatric curriculum at a 1000- bed university teaching hospital. We aimed to establish whether simulation helped to build confidence in dealing with paediatric emergencies ahead of Foundation training, and ascertained students' opinions of the value of simulation in undergraduate paediatric teaching. Methods: Final year medical students were briefed on the process of simulation and the basics of human factors in medicine. They then participated in three simulated paediatric emergencies, rotating through various roles. The students then completed an anonymous online feedback questionnaire, detailing previous experience of simulation, confidence prior to and following the simulation, their appreciation of human factors in paediatric emergencies, and their experience of post-simulation debriefing. Results: Of the students who completed the programme, the majority had previous experience in simulation. The number of students that felt confident in managing paediatric emergencies rose from 6% to 81% following the simulation session. 80% of participants felt that the simulation programme was successful in illustrating the role of human factors in paediatric emergencies. The medical students commented that the simulation was well organised, helpful and an effective method of learning. Conclusion: The students' responses demonstrate that simulation is a highly effective tool for increasing confidence in managing paediatric emergencies in preparation for Foundation training. In addition, most students felt that simulation was a beneficial and enjoyable method of teaching the need to maintain awareness of the central role that human factors play in paediatric emergencies. As a result of this project, we are expanding the provision of simulation within the paediatric curriculum to involve third year students from 2017.